1984
DOI: 10.1128/iai.45.2.443-446.1984
|View full text |Cite
|
Sign up to set email alerts
|

Phagosomal membranes of Mycobacterium bovis BCG-immune alveolar macrophages are resistant to disruption by Mycobacterium tuberculosis H37Rv

Abstract: Data obtained in this study reaffirm that virulent Mycobacterium tuberculosis H37Rv has a potent phagosome-destroying capacity when ingested by normal alveolar macrophages. In contrast, Mycobacterium bovis BCG-immune alveolar macrophages are highly resistant to this virulence mechanism. BCG-immune sera incubated with BCG-immune alveolar macrophages did not increase resistance of BCG-immune alveolar macrophages as compared with the data obtained from experiments with normal sera. BCG-immune sera failed to confe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 4 publications
(1 reference statement)
0
18
1
Order By: Relevance
“…On the other hand, one report states that virulent M. tuberculosis H37Rv bacilli can escape from the phagosome into the cytosol of normal rabbit alveolar macrophages whereas attenuated H37Ra bacilli cannot (26). Interestingly, a related study showed that the attenuated vaccine strain M. bovis BCG was also capable of escaping from the phagosomal membrane in normal rabbit alveolar macrophages although only a maximum of 25% of the ingested bacilli were found free in the cytoplasm (19). This study is in contrast to our findings, in which we were unable to show any cytolytic activity by this strain.…”
Section: The Plasmids Puc19 and Pbluescript Ii's-(stratagene)contrasting
confidence: 99%
“…On the other hand, one report states that virulent M. tuberculosis H37Rv bacilli can escape from the phagosome into the cytosol of normal rabbit alveolar macrophages whereas attenuated H37Ra bacilli cannot (26). Interestingly, a related study showed that the attenuated vaccine strain M. bovis BCG was also capable of escaping from the phagosomal membrane in normal rabbit alveolar macrophages although only a maximum of 25% of the ingested bacilli were found free in the cytoplasm (19). This study is in contrast to our findings, in which we were unable to show any cytolytic activity by this strain.…”
Section: The Plasmids Puc19 and Pbluescript Ii's-(stratagene)contrasting
confidence: 99%
“…The first reports of mycobacterial cytosolic localization are from 1984 (Leake et al ., 1984; Myrvik et al ., 1984); however, we are only now beginning to understand why this subcellular event is so often overlooked. Translocation, also often termed ‘escape’ is, however, well established as a virulence mechanism in several bacteria from other genera, including Shigella flexneri , Listeria monocytogenes , Burkholderia pseudomallei , Neisseria meningitidis , Rickettsia prowazekii and Francisella tularensis (Ray et al ., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…There have been reports over time providing evidence that M.tb can translocate into the cytosol of macrophages under defined conditions (Leake et al ., 1984; Myrvik et al ., 1984; McDonough et al ., 1993; van der Wel et al ., 2007) and also that mycobacterial phagosomes are porous (Teitelbaum et al ., 1999). Nonetheless, the weight of the evidence to date is that mycobacteria replicate in phagosomes in human and mouse macrophages.…”
Section: Discussionmentioning
confidence: 99%